A manifesto for social progress : ideas for a better society - Fleurbaey, Marc; Bouin, Olivier (Cambridge : Cambridge University Press, 2018)
At this time when many have lost hope amidst conflicts, terrorism, environmental destruction, economic inequality and the breakdown of democracy, this beautifully written book outlines how to rethink and reform our key institutions - markets, corporations, welfare policies, democratic processes and transnational governance - to create better societies based on core principles of human dignity, sustainability, and justice. This new vision is based on the findings of over 300 social scientists involved in the collaborative, interdisciplinary International Panel on Social Progress. Relying on state-of-the-art scholarship, these social scientists reviewed the desirability and possibility of all relevant forms of long-term social change, explored current challenges, and synthesized their knowledge on the principles, possibilities, and methods for improving the main institutions of modern societies. Their common finding is that a better society is indeed possible, its contours can be broadly described, and all we need is to gather forces toward realizing this vision.
Title from publisher's bibliographic system (viewed on 14 Sep 2018).
Keywords: Social policy; Economic policy; Equality; Democracy